An overview of the adsorption of glyphosate by different materials, natural, hybrid and composite - Hottes, Emanoel; Herbst, Marcelo Hawrylak (Seven Editora, 2023)
The present work brings a compilation of selected data on aspects involving the adsorption of glyphosate in aqueous medium by in different materials. According to the information reported, the pH of the medium plays a fundamental role in the formation of glyphosate anions, thus affecting its behavior in adsorption by different materials. It was found that the Langmuir and Freundlich isothermal models respond more satisfactorily to the glyphosate adsorption process as a function of the type of adsorbent, and that the adsorption mechanisms respond to a greater degree to a pseudo-second-order kinetic model  . Finally, it was found that clays, hybrid materials containing clays and biochar, were the matrices with the best adsorptive potential for glyphosate. DOI:https://doi.org/10.56238/alookdevelopv1-029